A case report of pulmonary amoebiasis with Entamoeba histolytica diagnosed in western Romania - Raul Neghina; Adriana A. Neghina; Carmen Merkler; Iosif Marincu; Ioan Iacobiciu (Journal of Infection in Developing Countries)
Background: Among parasitic diseases, amoebiasis is the third most frequent cause of mortality after malaria and schistosomiasis. Pulmonary amoebiasis, the second most common extraintestinal manifestation of infection, occurs in 2%-3% of patients with invasive amoebiasis. The present clinical report aims to present a single case of a rare diagnosed parasitic disease in Romania and to emphasize the difficulties encounted while attempting to establish the correct diagnosis and to completely cure the patient. Methodology: Retrospective analysis of all medical records of a patient hospitalized at Victor Babes Hospital of Infectious Diseases in Timisoara, Romania, and diagnosed with pulmonary amoebiasis. Results and Conclusions: The disease debuted in 1996 with intestinal symptomatology and was not diagnosed at that time. Thus evolution continued for another five years ending with the invasion of the lung. Differential diagnosis with a bacterial abscess, tuberculous abscess, and neoplastic disease were considered. A routine microscopic examination of the sputum finally clarified the diagnosis during a second hospitalization pointing out the importance of collaboration between the infectious disease clinicians and parasitologists.